Measuring Child Poverty - UNICEF Innocenti Research Centre (United Nations, 2012)
The United Nations Children’s Fund (UNICEF) - Innocenti Research Centre Report Card series provokes debate on child well-being in wealthy countries. It provides an important tool to address critical issues affecting disadvantaged children in the industrialized world. Since 2000, the Centre has released nine issues of the series, each addressing different aspects of the living conditions of children and adolescents. All the Report Cards are built around a league table, ranking countries according to their performance on a key child indicator or group of indicators. This issue investigates poverty and vulnerability among children in rich countries.